Archival Records of Environmental Hazards and Social Vulnerability to Disasters in Colonial Mauritius, c. 1857-1911 - Neerunjun, Helvina (International Journal of Social Sciences Review, 2024)
Small Island Developing States (SIDS) are characterised by their smallness and high exposure to global environmental challenges such as climate change. Although high exposure to physical environmental stressors over long periods of time may represent vulnerability, rich local knowledge can result in long histories of responding to disaster risk, demonstrating that smallness does not always lead to vulnerability. This research study focuses on environmental hazards in Colonial Mauritius and their impact on the Mauritian population from 1857 to 1911. Mauritius is one of those small islands with a colonial history and diseases prevalent during colonial times were considered to be a consequence of poverty, inadequate food supplies and bad sanitation. However, these factors alone did not account for the rapid spread of diseases. Climate variations often seemed to have influenced the incidence of illnesses in many tropical regions. Results showed that Islanders had to face several episodes of epidemics and water-borne diseases such as malaria were likely to increase and decrease after alternate periods of severe rainfall. Island studies on the spread of diseases and climate were increasingly recognised as offering valuable contributions to climate change adaptation in Mauritius. The mid-twentieth century marked the beginning of a new, prevention-oriented, colonial policy towards tropical cyclones and disease control. These catastrophes have led to a growing disaster consciousness in the Mauritian community, and over time, strengthened the coordination ability of institutions to shape the modern-day perspectives of the Mauritian Society.